2013
DOI: 10.1021/es403605f
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Plastic: A Source and Sink for Polycyclic Aromatic Hydrocarbons in the Marine Environment

Abstract: Polycyclic aromatic hydrocarbons (PAHs) on virgin polystyrene (PS) and PS marine debris led us to examine PS as a source and sink for PAHs in the marine environment. At two locations in San Diego Bay, we measured sorption of PAHs to PS pellets, sampling at 0, 1, 3, 6, 9 and 12 months. We detected 25 PAHs using a new analytical method with comprehensive two-dimensional gas chromatography coupled to time-of-flight mass spectrometry. Several congeners were detected on samples before deployment. After deployment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
131
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(145 citation statements)
references
References 45 publications
(128 reference statements)
8
131
0
6
Order By: Relevance
“…Microplastics are commonly found in the environment in three forms; fragments which form from mechanical and biological fragmentation of larger plastic items (ter Halle et al, 2016), microbeads which are manufactured as abrasives in cosmetics and air-blasting (Fendall and Sewell, 2009;Mason et al, 2016), and microfibers from sources such as synthetic fabrics and ropes (Browne et al, 2011). Studies have shown multiple damaging effects of microplastics in the environment, including adsorption of toxic organic contaminants (Endo et al, 2005;Teuten et al, 2007;Rochman et al, 2013), ingestion by animals with implications for human consumption (Van Cauwenberghe and Janssen, 2014;Rochman et al, 2015) and changing the heat transfer and water movement of sediment (Carson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics are commonly found in the environment in three forms; fragments which form from mechanical and biological fragmentation of larger plastic items (ter Halle et al, 2016), microbeads which are manufactured as abrasives in cosmetics and air-blasting (Fendall and Sewell, 2009;Mason et al, 2016), and microfibers from sources such as synthetic fabrics and ropes (Browne et al, 2011). Studies have shown multiple damaging effects of microplastics in the environment, including adsorption of toxic organic contaminants (Endo et al, 2005;Teuten et al, 2007;Rochman et al, 2013), ingestion by animals with implications for human consumption (Van Cauwenberghe and Janssen, 2014;Rochman et al, 2015) and changing the heat transfer and water movement of sediment (Carson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges for the development of thermal processing of MSW is the production of pollutants such as polycyclic aromatic hydrocarbons (PAH) (Rochman et al, 2013;Hajizadeh et al, 2011). There is some concern over the emissions of PAH in the environment (Sun et al, 1998), since they are associated with human teratogenesis, cancer or mutations, with a bioaccumulative effect (Samanta et al, 2002;Moeckel et al, 2014;Ionescu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2 However, there are several challenges for the copyrolysis of biomass and plastics towards large-scale development; for example, the formation of polycyclic aromatic hydrocarbons (PAH) in the product oil. 3 PAH are a group of semi-volatile hydrocarbons, which may cause teratogenesis, cancer or mutations if absorbed by the human body. 4 Due to the large number and complex nature of PAH compounds, 16 PAH (naphthalene, acenaphthylene, acenaphthene etc.)…”
Section: Introductionmentioning
confidence: 99%